Unhealthy Business Competition in Government Procurement of Goods/Services in Indonesia: An Analysis of the Friedman Legal System - Zaenal Arifin; Arief Slamet Karyadi; Miftah Arifin (JUSTISI, 2026)
This study aims to analyze unfair business competition practices and their resolution mechanisms in government procurement of goods and services in Indonesia using Lawrence M. Friedman's legal system theoretical framework. The study method used is normative legal research with a legislative, conceptual, and case study approach, which is analyzed qualitatively through a review of legislation, decisions of the Business Competition Supervisory Commission (KPPU), and relevant legal literature. Case studies were conducted by analyzing three KPPU decisions that represent patterns of tender collusion in procurement, namely the Revitalization of Taman Ismail Marzuki (TIM) Phase III case, the provision of clean water in North Lombok, and the construction of the Prabumulih Mall. The novelty of this research lies in the simultaneous integration of weaknesses in legal structure, legal substance, and legal culture to assess the effectiveness of antitrust law enforcement in the procurement sector. The results of the study show that the main obstacles to the enforcement of business competition law not only stem from regulatory loopholes and definitions of norms that are not yet operational, but are also influenced by institutional capacity constraints, weak inter-agency coordination, and a permissive culture towards collusion in procurement practices. This study emphasizes that strengthening the effectiveness of law enforcement requires practical measures such as refining the norms prohibiting collusion, integrating sanctions and a database of violations into the national e-procurement system, and strengthening the synergy between KPPU and LKPP through a post-decision monitoring mechanism to prevent repeat violations. The conclusion of the study states that regulatory reformulation, strengthening of supervisory institutions, and renewal of the culture of compliance are key prerequisites for the realization of transparent, fair, and accountable procurement governance.